Representasi Konflik Remaja dalam Film Jumbo Karya Ryan Adriandhy dan Pemanfaatannya sebagai Bahan Ajar Teks Resensi di Sekolah Menengah Kejuruan - Madya Nur Fadzila; Kundharu Saddhono (Universitas Palangka Raya, 2026)
This study aims to describe the representation of adolescent conflicts in the film Jumbo directed by Ryan Adriandhy and to analyze its relevance as teaching material for review text learning in vocational high schools. This research employed a descriptive qualitative approach using content analysis. The data consisted of dialogues, scenes, character expressions, plot, and cinematic elements representing adolescent conflicts in the film. Data sources included the film Jumbo, interviews with Indonesian language teachers and eleventh-grade students at SMK PGRI 1 Surakarta, and review text learning documents. Data were collected through observation, documentation, and semi-structured interviews, then analyzed using the Miles and Huberman model. Stuart Hall’s representation theory was used as the analytical framework. The findings show that the film represents identity, family, friendship, and social conflicts experienced by adolescents. These conflicts are constructed through dialogues, visuals, character relationships, and plot development. Furthermore, the film is relevant as teaching material for review text learning because it helps students understand story elements, increases learning engagement, and develops analytical, evaluative, and critical thinking skills. However, students still need guidance in distinguishing summaries from evaluations in review texts.